The Advantage Of Oil Content In Injection Water Determination Before Implementation Of Waterflood In Oilfield - Tjuwati Makmur (Testing Center for Oil and Gas LEMIGAS, 2010)
Before implementation of water flooding in oilfield, it will be good to determine oil content in the injection water. The results of laboratory tests provide valuable and useful information, firstly, whether reverse demulsifier is required or not to reduce oil content in water. Secondly, the test results can select the effective reverse demulsifier. S1 and S2 injection water contain very low oil content, so it is not necessary to add reverse demulsifier in the both injection water. High oil content is obtained in S3 injection. The 50 mg/L DKM reverse demulsifier does not work effectively to reduce oil content in the S3 injection water. Whereas, the 50 mg/L Prolab reverse demulsifier is effective and able to reduce oil content sharply in the S3 injection water with 95.46 % efficiency.